Implementasi Nilai -Nilai Pancasila dalam kegiatan PKK di Desa Sirnoboyo Kecamatan pacitan Kabupaten Pacitan - Achmad Ridlowi (Transformasi : Jurnal Studi Agama Islam, 2017)
Pancasila  as  a  way  of  life  requires  Indonesia  to  transform  the values  of Pancasila in a real and continuous appreciation and practice of noble  values  contained  in  it  by  every  citizen  of  Indonesia,  each  state officials as well as any institutions of state and civil society, both in the center or  in the region. In social  life there  is one activity that embodies the implementation of Pancasila values  through the activities of the PKK (Family Welfare Empowerment) is an activity initiated by the women in i t has several programs to run 10 (ten) program PKK with the single goal welfare of the family. The grounds are one of the main programs in the PKK, namely The Pancasila, women as objects of research because as the creator  of  the  next  generation  of  national   struggle,  and  in  2015  this village  Sirnoboyo  used  as  guided  village  PKK  is  as  active  village  and most diligently implement programs PKK.Factors supporting the  live  in  harmony between people,  there  is no specific provision to follow the activities of the  PKK, the evaluation of performance  management to produce a  nice,  family and community support. Inhibiting factors: the chairman of the PKK in the actual practice of  not carrying out the duties as chairman of  the task,  not  yet aware of their rights and obli gations.